Stone Milling versus Roller Milling in Soft Wheat (Part 2): Influence on Nutritional and Technological Quality of Products - Marina Carcea; Valentina Narducci; Valeria Turfani; Enrico Finotti (Foods, 2022)
Wholegrain soft wheat flours can be obtained by either roller milling or stone milling. In this paper, we report on the continuation of a study aimed at analysing compositional and technological differences between differently milled wholegrain flours. Eight mixes of soft wheat grains were stone milled and roller milled and the milling products analysed for their phytic acid, lipids composition to determine the presence of trans-fatty acids and damaged starch. A wholegrain flour milled with a laboratory disk mill was also analysed as comparison, as well as seven wholegrain flours purchased on the market. For phytic acid we found that that there is no compositional difference between a stone milled or a roller milled flour if the milling streams are all recombined: the milling streams instead have different amounts of phytic acid which is mainly present in the fine bran and coarse bran. It was not possible to highlight differences in the milling technology due to the presence of trans-fatty acids in the stone milled wholegrain flour whereas it was possible to find that starch damage depended on the milling method with stone milled wholegrain flours having in all cases significantly higher values than the roller milled ones.